PEMBERDAYAAN MASYARAKAT PETANI RUMPUT LAUT DI KABUPATEN HALMAHERA SELATAN (Studi Desa Mano Kecamatan Obi Selatan) - Suhu, Bakri La; Wance, Marno (Program Studi Ilmu Pemeritahan Fakultas Ilmu sosial dan Ilmu Politik Universitas 17 Agustu, 2019)
This study aims to find out the form of comunity of seaweed farming and the factors that inhibit the farming community in developing seaweed cultivation in Mano Village, South Obi Subdistrict, South Halmahera Regency. Using descriptive qualitative research as a research procedure that produces descriptive data in the form of written or oral words from people and observable behavior, This study is design explain things or problems that occur and are described according to the focus of the research problem. Data sources used are primary data and secondary data. Inahich data the collection are through observation, interviews and documents analysis.Based on the result of the study, it shows that there are several forms of empowerment program of the Mano seawid Regional Government in this marine office of the South Halmahera District case and Fisheries Service, including (1) the establishment of seaweed farmer groups, the formation of graps support this group was from 2011 to 2015 and now there are 19 groups of seaweed farmers, (2) Providing in the form of production equipment in the form of “pelompong” and seawed drying, but the assistance provided is not fully distributed to 19 groups due to limited budget so that assistance in the form of pelompong is only 192 units for 5 groups and seawed drying equipment 16 units for only 2 groups. While the inhibiting factors of farmers in cultivnting seawed include (1) lack of marketing program to sell the seaweed, (2) lack of business capital in the development of seaweed cultivation, and (3) absence of training and counseling activities on dewed cultivation for the farming communities.